Solve for y 2x+6y=-18

Math
2x+6y=-18
Subtract 2x from both sides of the equation.
6y=-18-2x
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6y=-18-2x by 6.
6y6=-186+-2×6
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6y6=-186+-2×6
Divide y by 1.
y=-186+-2×6
y=-186+-2×6
Simplify each term.
Tap for more steps…
Divide -18 by 6.
y=-3+-2×6
Cancel the common factor of -2 and 6.
Tap for more steps…
Factor 2 out of -2x.
y=-3+2(-x)6
Cancel the common factors.
Tap for more steps…
Factor 2 out of 6.
y=-3+2(-x)2(3)
Cancel the common factor.
y=-3+2(-x)2⋅3
Rewrite the expression.
y=-3+-x3
y=-3+-x3
y=-3+-x3
Move the negative in front of the fraction.
y=-3-x3
y=-3-x3
y=-3-x3
Solve for y 2x+6y=-18

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top